Rapid evaluation of the extent in micro-degradation of protective coatings using laser-ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). (1st January 2011) - Fok, S.C.; Pillay, Avin E.; Stephen, Sasi; Abd-Elhameed, Amr
The durability of coatings used to protect base materials can be affected by environmental factors and degradation mechanisms including thermal decomposition, catalytic decomposition, bio-disintegration, chemical corrosion and mechanical scission. LA-ICP-MS is often used for the analysis of the trace elements to understand the degradation mechanism. This article extends the use of the LA-ICP-MS for the determination of the extent of coating degradation. The method is particularly useful for the rapid evaluation of conventional overlay metal-coatings at micron and sub-micron levels in applications such as pipelines commonly found in the oil and gas industry.